Philosophy and organization theory - Tsoukas, Haridimos; Chia, Robert C. H., 1949- (Emerald, 2011)
What is the relationship between philosophy and organization theory (OT)? While at first glance there might appear to be little, a closer look reveals a rich pattern of connections. More than any other type of human inquiry, philosophy helps make us self-aware of critical assumptions we tacitly incorporate in our organizational theorizing; it creates a deeper awareness of the unconscious metaphysics underpinning our efforts to understand organizations. There are at least three ways in which philosophical analysis is connected with organizational research: ontological, epistemological, and praxeological. To wonder about what the phenomena we investigate are constituted by, how we may obtain knowledge of them, and how that knowledge is related to action, is to begin to think philosophically about OT. Philosophical questions are higher-order questions - meta to OT as a scientific discipline; they are generated from outside the frameworks within which organizational scientists carry out their research practices. When the very frameworks of scientific inquiry, hitherto tacitly accepted for the practice of scientific research to be carried out, become questionable, philosophical reflection enters the scene. Philosophy keeps meaning open in a scientific field. Papers in this volume explore connections between several streams in philosophy and OT. As the titles of the papers suggest, most authors write about a particular philosopher or group of philosophers that make up a distinct school of thought, summarize important aspects of his/their work, and tease out the implications for OT. The central question authors explore is: what does a particular philosophy contribute to OT? Either addressing this question in historical or exploratory terms, or in a combination of both, the end result is similar: particular philosophical issues, properly explained, are discussed in relation to important questions in OT.
Keywords: Organizational sociology.; elektronické knihy; electronic books